Camino ghosts : a novel - Grisham, John (New York : Random House Large Print, 2024)
"In this new thriller on Camino Island, popular bookseller Bruce Cable tells Mercer Mann an irresistible tale that might be her next novel. A giant resort developer is using its political muscle and deep pockets to claim ownership of a deserted island between Florida and Georgia. Only the last living inhabitant of the island, Lovely Jackson, stands in its way. What the developer doesn't know is that the island has a remarkable history, and locals believe it is cursed...and the past is never the past...
Keywords: Antiquarian booksellers -- United States -- Fiction; Bookstores -- Fiction; Novelists -- Fiction; Islands -- Fiction; Real estate developers -- Fiction; Landowners -- Fiction; Blessing and cursing -- Fiction; Resorts -- Fiction; Large type books; Florida -- Fiction; Large type books; Thrillers (Fiction); Detective and mystery fiction; Large print books